2009
DOI: 10.3899/jrheum.081090
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Clinically Important Difference in the Fibromyalgia Impact Questionnaire

Abstract: The analysis indicates that a 14% change in the FIQ total score is clinically relevant, and results of these analyses should enhance the clinical utility of the FIQ in research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
248
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(269 citation statements)
references
References 28 publications
14
248
0
7
Order By: Relevance
“…In other studies evaluating patients with comorbid MDD and fibromyalgia, the severity of depression was usually in the mild range (i.e., HAM-D score 10-15) with less severe impairment due to fibromyalgia (i.e., FIQ score Ͻ60) (20,39). The change from baseline to week 8 in the FIQ score meets the threshold for the minimal clinically important difference (14%) (46), supporting a meaningful improvement in fibromyalgia symptoms with quetiapine XR.…”
Section: Discussionmentioning
confidence: 98%
“…In other studies evaluating patients with comorbid MDD and fibromyalgia, the severity of depression was usually in the mild range (i.e., HAM-D score 10-15) with less severe impairment due to fibromyalgia (i.e., FIQ score Ͻ60) (20,39). The change from baseline to week 8 in the FIQ score meets the threshold for the minimal clinically important difference (14%) (46), supporting a meaningful improvement in fibromyalgia symptoms with quetiapine XR.…”
Section: Discussionmentioning
confidence: 98%
“…However, a higher reduction rates in the FIQ score and BDI score have been suggested as clinically significant by some authors [28]. In a recent study by Yilmaz et al [29] including patients with chronic nonspecific widespread musculoskeletal pain, it was reported that replacement of vitamin D improved the quality of life (SF-36).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects' FIQ total scores were used to define fibromyalgia severity as follows: 0 to less than 39 = mild, 39 to less than 59 = moderate, and 59 to 100 = severe. 25 …”
Section: Patient Questionnaire and Assessment Of Fibromyalgia Severitymentioning
confidence: 99%